Testing content validity of teacher-made test: Profiling teacher perceptions and demographic variables - Mohammed Borhandden Musah; Lokman Mohd Tahir; Shafeeq Hussain Al-Hudawi; Mohammad Issah; Abdul Rawuf Hussein; Mikail Ibrahim (Institute of Advanced Engineering and Science, 2022)
The content validity of teacher-made tests (TMT) in Malaysian Chinese primary schools was explored in this research. The study used teacher-made tests to analyze the selected Chinese primary schools, which have yet to be thoroughly explored in the context of these school types. It also investigated how well teachers in the sampled schools understand the table of specifications (TOS). The study further examined the extent to which included demographic variables affect the validity of teacher-made tests. A total of 660 questionnaires were distributed randomly to teachers from 21 Chinese primary schools. There were 381 completed questionnaires (58% of total rate) received and analyzed. The findings demonstrated that most teachers have a basic understanding of the TOS and that teacher-made test levels are valid. K-group MANOVA analysis also revealed that work experience and age had a significant influence on teacher understanding. Work experience and age, on the other hand, had no effect on the teacher-made test. Furthermore, the findings demonstrated that both teacher understanding and teacher-made tests were unaffected by teacher gender.